Co3O4-NP embedded mesoporous carbon rod with enhanced electrocatalytic conversion in lithium-sulfur battery. Issue 1 (December 2018) - Wang, Shaofeng; Hou, Xianhua; Zhong, Zeming; Shen, Kaixiang; Zhang, Guangzu; Yao, Lingmin; Chen, Fuming
Abstract Lithium-sulfur battery has been considered to be one of the promising alternatives to the traditional lithium-ion battery due to its high theoretical energy density and saving-cost. However, the sluggish reaction during the decomposition of lithium sulfide results in a low specific capacity and poor cycling stability. Herein Co3 O4 nano-particle embedded mesoporous carbon rod (Co3 O4 @MCR) was prepared through a template method to accommodate sulfur as cathode of lithium-sulfur battery. The resultant composite was characterized by Raman spectra, XRD, TEM, SEM, etc. The electrochemical investigation demonstrated that Co3 O4 @MCR composite exhibits enhanced electrocatalytic performance in lithium-sulfur battery, which was confirmed by cyclic voltammograms, galvanostatic charge-discharge testing, and study of sulfide oxidation using linear sweep voltammetry. With the current density of 0.2 A/g, the specific discharge capacity can be achieved up to more than 1000 mAh/g after 100 cycles. The enhanced electrocatalytic conversion from Co3 O4 @MCR leads to a low over-potential, fast lithium-ion kinetics and sulfide oxidation reaction.